2016
DOI: 10.4329/wjr.v8.i4.378
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of primary bone tumors: A case control study

Abstract: AIM:To study the safety and effectiveness of preoperative embolization of primary bone tumors in relation to intraoperative blood loss, intraoperative blood transfusion volume and surgical time. METHODS:Thirty-three patients underwent preoperative embolization of primary tumors of extremities, hip or vertebrae before resection and stabilization. The primary osseous tumors included giant cell tumors, aneurysmal bone cyst, osteoblastoma, chondroblastoma and chondrosarcoma. Twenty-six patients were included for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…One of the parameters that we considered in our research was the amount of bleeding. In a study by Jha et al, measurements was made by weighing bloody gauze to estimate the amount of bleeding (20). However, since there was not a lot of blood loss in our research, we preferred the method we described earlier (13).…”
Section: Discussionmentioning
confidence: 99%
“…One of the parameters that we considered in our research was the amount of bleeding. In a study by Jha et al, measurements was made by weighing bloody gauze to estimate the amount of bleeding (20). However, since there was not a lot of blood loss in our research, we preferred the method we described earlier (13).…”
Section: Discussionmentioning
confidence: 99%
“…Since preoperative embolization was first introduced in 1975, it has been shown to decrease intraoperative bleeding, allowing for decreased rates of required blood transfusion and better surgical outcomes [13]. Bone tumors that are often aided by preoperative embolization are commonly hypervascular, such as giant cell and renal cell tumors [13]. A successful preoperative embolization is the reduction of >70% of the vascularization, performed within 72 hours of surgery [6].…”
Section: Discussionmentioning
confidence: 99%
“…A successful preoperative embolization is the reduction of >70% of the vascularization, performed within 72 hours of surgery [6]. A case-control study conducted in 2016 reported a less amount of intraoperative blood loss and blood transfusion requirements in patients who received a preoperative embolization procedure for a primary bone tumor versus those that did not [13]. Geraets et al performed a systematic review that showed supporting evidence for preoperative embolization of RCC metastasis but not those from other primary tumors, including thyroid metastasis [6].…”
Section: Discussionmentioning
confidence: 99%
“…It was published by Roshan Jha et al in 2016 comparing 26 patients who underwent pre-operative embolisation with 28 patients in the control group (without pre-embolisation). The mean estimated blood loss (EBL) for the pre-embolised group was 1300ml and the non-embolised group was 1800ml 20 . Table 4 showed comparison of estimated and mean blood loss from our study in comparison with other studies from literature reviews .…”
Section: Discussionmentioning
confidence: 99%